The relationship between social media engagement, eating disorders and body image concern among undergraduate students - Nur Zakiah Mohd Saat; Siti Aishah Hanawi; Hazlenah Hanafi; Prema Muthiah; Fatin Farhana Jubaidi; Farahnaz Ahmad Anwar@Anwar Bashar; Sharifah Nadhira Syed Annuar (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the contemporary university landscape, social media stands as a pivotal force shaping the academic, social, and personal lives of students. With its ubiquitous presence, platforms like Facebook, Instagram, Twitter, and TikTok have become integral tools for communication, networking, and self-expression among university students worldwide. The relationship between social media, eating behavior, and body image among university students is complex and multifaceted, influenced by various psychological, social, and cultural factors. This study aimed to determine the association between social media engagement, eating disorder severity and body image concern among undergraduate students. A quantitative cross-sectional study was conducted among 131 university students. A self- administered questionnaire was utilized which consists of socio-demographic data, social media engagement, eating disorder severity and body image concern. Analysis showed that association of social media engagement and eating disorder severity was found to be higher in female students while interestingly, body image concern was higher in male students. Moreover, eating disorder was associated significantly with social media based on correlation test(r=0.204,p<0.05). Overall, social media engagement, eating disorder severity and body image concern were positively correlated to one another. The results indicated that social media usage plays an important role in influencing eating patterns and physical appearance concern. Further studies that included concern on self-esteem in the study factors and diverse samples are highly recommended to thoroughly elucidate the relationship between social media, eating disorder, body image and self-esteem concerns among students.